Pengaruh Penggunaan Alat Peraga Jam Sudut terhadap Hasil Belajar Matematika - Handoyo Heru Binangun; Arif Rahman Hakim (Universitas Indraprasta PGRI, 2016)
The aim of the experiment research is to know the effect of using prop of the clock angle on mathematics achievement. The benefit of this research is to improve the knowledge, especially in mathematics field through creation and innovation of prop that is used in learning process. The research design that is used is true experimental design in the form of posttest only control design. This experiment was conducted in the seventh grade of PGRI Junior High School Tenjolaya Bogor, even semester in academic year 2015/2016. Sample was taken randomly, it was two groups, they are experiment group and control group. After giving different treatment for each group, then posttest in the multiple choices form that consist of 4 alternative answers for each group was given. The instrument that was used in this research has been tested, and all items were valid and reliable. Data analysis used t test, normality and homogenity test has been tested first. The result of the research show that there is a significant effect of using prop of the clock angle on mathematics achievement in the seventh grade of PGRI Junior High School Tenjolaya Bogor, especially for angle material.